2006
DOI: 10.1159/000092680
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Growth Hormone on Superoxide Dismutase Activity, Glutathione and Malondialdehyde Levels of Hypoxic-Ischemic Newborn Rat Brain

Abstract: Objectives: We investigated the effect of human growth hormone (GH) on newborn rat brain superoxide dismutase, glutathione and malondialdehyde (MDA) levels in hypoxic-ischemic (H-I) newborn rats. Methods: Fourty-eight 7 days old newborn rats were randomized to a healthy (n: 15), H-I (n: 18) and GH administered H-I (GH-H-I, n: 15) group. Permanent, left common carotid ligation was performed in the H-I groups. In the GH-H-I group, 50 mg/kg human GH (Norditropin Simplex, Novo Nordisk A/S) was administered subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The data on GSH content in the brain or brain structures after neonatal H/HI are somewhat contradictory and there is an evidence of structural and time‐dependent manner of these changes. Most studies found no change in GSH level immediately after and within 2 h after HI (Dafre et al, 2003; Wallin et al, 2000; Yapicioǧlu et al, 2006) or hypoxia alone (Greggio et al, 2009; Kletkiewicz et al, 2016). The GSH content was decreased at 3–72 h after H/HI (Bratek et al, 2018; Dafre et al, 2003; Greggio et al, 2009; Kaur et al, 2010; Wallin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The data on GSH content in the brain or brain structures after neonatal H/HI are somewhat contradictory and there is an evidence of structural and time‐dependent manner of these changes. Most studies found no change in GSH level immediately after and within 2 h after HI (Dafre et al, 2003; Wallin et al, 2000; Yapicioǧlu et al, 2006) or hypoxia alone (Greggio et al, 2009; Kletkiewicz et al, 2016). The GSH content was decreased at 3–72 h after H/HI (Bratek et al, 2018; Dafre et al, 2003; Greggio et al, 2009; Kaur et al, 2010; Wallin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Human growth hormone was found to increase lipid peroxidation in rats which in turn increases MDA level of hypoxic-ischemic newborn rat brain tissue [33].…”
Section: Mda In Ischemic Conditionsmentioning
confidence: 95%